Dissecting aggregation and seeding dynamics of α-Syn polymorphs using the phasor approach to FLIM - Tittelmeier, Jessica; Druffel-Augustin, Silke; Alik, Ania; Melki, Ronald; Nussbaum-Krammer, Carmen (Communications biology, 2022)
Synucleinopathies are a heterogenous group of neurodegenerative diseases characterized by the progressive accumulation of pathological α-synuclein (α-Syn). The importance of structural polymorphism of α-Syn assemblies for distinct synucleinopathies and their progression is increasingly recognized. However, the underlying mechanisms are poorly understood. Here we use fluorescence lifetime imaging microscopy (FLIM) to investigate seeded aggregation of α-Syn in a biosensor cell line. We show that conformationally distinct α-Syn polymorphs exhibit characteristic fluorescence lifetimes. FLIM further revealed that α-Syn polymorphs were differentially processed by cellular clearance pathways, yielding fibrillar species with increased seeding capacity. Thus, FLIM is not only a powerful tool to distinguish different amyloid structures, but also to monitor the dynamic process of amyloid remodeling by the cellular environment. Our data suggest that the accumulation of highly seeding competent degradation products for particular polymorphs may account for accelerated disease progression in some patients.